2019
DOI: 10.1002/jcp.29341
|View full text |Cite
|
Sign up to set email alerts
|

Cell mechanical microenvironment for cell volume regulation

Abstract: Cell volume regulation, as one of the fundamental homeostasis of the cell, is associated with many cellular behaviors and functions. With the increased studies on the effect of environmental mechanical cues on cell volume regulation, the relationship between cell volume regulation and mechanotransduction becomes more and more clear. In this paper, we review the mechanisms and hypotheses by which cell maintains its volume homeostasis both in vivo and in constructed cell mechanical microenvironment (CMM) in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 98 publications
(212 reference statements)
0
20
0
Order By: Relevance
“…Moreover, cell volume changes are also key in regulating the lumen volume of intestinal organoids (Yang et al, 2021) and the K€ upffer vesicle morphogenesis in zebrafish (Dasgupta et al, 2018). In vitro, external mechanical cues such as cell matrix stiffness can trigger cell volume changes (Guo et al, 2017;Wang et al, 2020;Xie et al, 2018). In addition, cell volume is controlled by osmotic regulation, cell cytoskeletal contractility, and cell growth and division (Cadart et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cell volume changes are also key in regulating the lumen volume of intestinal organoids (Yang et al, 2021) and the K€ upffer vesicle morphogenesis in zebrafish (Dasgupta et al, 2018). In vitro, external mechanical cues such as cell matrix stiffness can trigger cell volume changes (Guo et al, 2017;Wang et al, 2020;Xie et al, 2018). In addition, cell volume is controlled by osmotic regulation, cell cytoskeletal contractility, and cell growth and division (Cadart et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cell volume regulation is one of the fundamental homeostasis of the cell that is associated with various cellular behaviours and functions. 25 , 26 Additionally, the disorder of cell volume homeostasis has been reported to be linked to the pathogenesis and progression of several diseases. 27 After the mesothelial injury, mesothelial cells undergo tissue recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, we determined that MMP‐7 could up‐regulate the cell volume of mesothelial cells. Cell volume regulation is one of the fundamental homeostasis of the cell that is associated with various cellular behaviours and functions 25,26 . Additionally, the disorder of cell volume homeostasis has been reported to be linked to the pathogenesis and progression of several diseases 27 .…”
Section: Discussionmentioning
confidence: 99%
“… 19–21 We know that changes in the osmotic pressure of the cell’s environment will affect the volume of the cell and cause a series of changes in subsequent physiological and metabolic cell processes. 22 Research by Yamada and other scholars has shown that, in healthy joints, articular cartilage cells are exposed to an overall relatively hypertonic dynamic osmotic environment and protect themselves from swelling and destruction through regulatory volume decrease (RVD). Furthermore, if the cell is in a relatively hypotonic environment for a long time and the pathological change in osmotic pressure exceeds the threshold of cell self-regulation, its RVD mechanism can no longer fully compensate, and the cell will continue to swell until death, triggering OA.…”
Section: Extracellular Microenvironment and The Pathogenesis Of Oamentioning
confidence: 99%